Alteration of various lipids in pregnancies complicated by hypertensive disorders - Priyadarshini, Mona; Hansda, Rita (Eastern Journal of Medical Sciences, 2020)
Background: Preeclampsia is a common medical problem associated with pregnancy with substantial risk to the mother and fetus. Abnormal lipid metabolism seems important in the pathogenesis of pregnancy-induced hypertension. Objective: The objective was to study the alteration of various lipids in pregnancies complicated by hypertensive disorders. Materials and Methods: This prospective study was conducted among 150 pregnant women in the department of obstetrics and gynecology, from September 2009 to May 2011. The subjects were divided into two groups of normotensive women and women with complicated pregnancy by hypertensive disorder with 75 patients each. Serum lipid profile including total cholesterol, triglyceride (TG), low-density lipoprotein (LDL), and high-density lipoprotein (HDL) was determined and compared between the two groups. The data were analyzed using the Chi-square test and analysis of variance test. p